Biodiversity, food webs and an ecologically safe space for fisheries - Christopher P. Lynam; Robert B. Thorpe; Murray S.A. Thompson (Fisheries Research, 2026)

Ecological recovery of benthic fauna from contamination near oil and gas platforms - Christopher P. Lynam; Clement Garcia; Zelin Chen; Gareth E. Thomas; Natalie Hicks; Stefan G. Bolam; Debbie J.F. Russell (Marine Pollution Bulletin, 2025)

‘Horses for courses’ – an interrogation of tools for marine ecosystem-based management - Nadia Papadopoulou; Christopher John Smith; Anita Franco; Michael Elliott; Angel Borja; Jesper H. Andersen; Eva Amorim; Jon P. Atkins; Steve Barnard; Torsten Berg; Silvana N. R. Birchenough; Daryl Burdon; et al. (Frontiers in Marine Science, 2025)
Marine Ecosystem-Based Management (EBM) approaches are a well-established and fundamental component of international agreements and treaties, regional seas conventions, assessment strategies, European Directives and national and regional instruments. However, there is the need to interrogate and clarify the implementation of EBM approaches under current marine management. Although particular focus here is within the European Union Marine Strategy Framework Directive (MSFD), all lessons learned are applicable to marine assessments and management in seas worldwide given that all marine management instruments aim to ensure sustainability in marine ecosystems and human uses. Notably, the MSFD aims to ensure that Good Environmental Status (GES) will be achieved thereby enabling the sustainability of coastal and marine ecosystems to deliver ecosystem services and societal goods and benefits while at the same time being adaptive to rapid climate and environmental changes. As a clear understanding of EBM and the tools available to achieve it is needed for practitioners, regulators and their advisors, the analysis here firstly presents the current understanding of EBM (including its origin and application) and the wider 26 principles on which it is based. Secondly, we identify the key elements that are addressed by those principles (18 key EBM elements). Thirdly, we identify the types of tools available for use in the EBM context (19 tool groups). Fourthly we analyze the suitability of tool types to deliver the key EBM elements using an expert judgement approach. Finally, we conclude with the lessons learned from the use of those tools and briefly indicate how they could be combined to help achieve EBM in the most effective way. It is emphasized that no single tool is likely to satisfy all aspects of EBM and therefore employing a complementary suite of tools as part of a toolbox is recommended.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Climate change affects the distribution of diversity across marine food webs - Murray S. A. Thompson; Elena Couce; Michaela Schratzberger; Christopher P. Lynam (Global Change Biology, 2023)
Many studies predict shifts in species distributions and community size composition in response to climate change, yet few have demonstrated how these changes will be distributed across marine food webs. We use Bayesian Additive Regression Trees to model how climate change will affect the habitat suitability of marine fish species across a range of body sizes and belonging to different feeding guilds, each with different habitat and feeding requirements in the northeast Atlantic shelf seas. Contrasting effects of climate change are predicted for feeding guilds, with spatially extensive decreases in the species richness of consumers lower in the food web (planktivores) but increases for those higher up (piscivores). Changing spatial patterns in predator–prey mass ratios and fish species size composition are also predicted for feeding guilds and across the fish assemblage. In combination, these changes could influence nutrient uptake and transformation, transfer efficiency and food web stability, and thus profoundly alter ecosystem structure and functioning.

Synthesizing Empirical and Modelling Studies to Predict Past and Future Primary Production in the North Sea - Michael A. Spence; Christopher P. Lynam; Robert B. Thorpe; Ryan F. Heneghan; Paul J. Dolder (Frontiers in Marine Science, 2022)
Understanding change at the base of the marine foodwebs is fundamental to understanding how climate change can impact fisheries. However, there is a shortage of empirical measurements of primary productivity, and models estimates often disagree with each other by an order of magnitude or more. In this study we incorporate information from empirical studies and a suite of Earth system models statistically downscaled using an ensemble model to produce estimates of North Sea primary production with robust quantification of uncertainties under two different climate scenarios. The results give a synthesised estimate of primary production that can feed into regional fisheries models. We found that Earth system models describe the dynamics of primary production in the North Sea poorly, and therefore the effects of climate change on future primary production are uncertain. The methods demonstrated here can be applied to other geographical locations and are not limited in application to primary production.

The Response of North Sea Ecosystem Functional Groups to Warming and Changes in Fishing - Robert B. Thorpe; Nina L. Arroyo; Georges Safi; Nathalie Niquil; Izaskun Preciado; Michael Heath; Matthew C. Pace; Christopher P. Lynam (Frontiers in Marine Science, 2022)
Achieving Good Environmental Status (GES) requires managing ecosystems subject to a variety of pressures such as climate change, eutrophication, and fishing. However, ecosystem models are generally much better at representing top-down impacts from fishing than bottom-up impacts due to warming or changes in nutrient loading. Bottom-up processes often have to be parameterised with little data or worse still taken as a system input rather than being represented explicitly. In this study we use an end-to-end ecosystem model (StrathE2E2) for the North Sea with 18 broad functional groups, five resource pools, and representations of feeding, metabolism, reproduction, active migrations, advection, and mixing. Environmental driving data include temperature, irradiance, hydrodynamics, and nutrient inputs from rivers, atmosphere, and ocean boundaries, so the model is designed to evaluate rigorously top-down and bottom-up impacts and is ideal for looking at possible changes in energy flows and “big picture” ecosystem function. In this study we considered the impacts of warming (2 and 4°C) and various levels of fishing, by demersal and pelagic fleets, on the structure and function of the foodweb. A key aim is to demonstrate whether monitoring of broad ecosystem groups could assist in deciding whether GES was being achieved. We found that warming raised primary productivity and increased the size (total biomass) of the ecosystem. Warming raised metabolic demands on omnivorous zooplankton and reduced their abundance, thus favouring benthivorous and piscivorous demersal fish at the expense of planktivorous pelagic fish but otherwise had modest effects on energy pathways and top predators, whereas changes in fishing patterns could materially alter foodweb function and the relative outcomes for top predators. We suggest that GES should be defined in terms of an unfished state and that abundances of broad groupings and the balance between them can help to assess whether indicator outcomes were consistent with GES. Our findings underwrite the need for an ecosystem approach for the management of human activities supported by relevant monitoring. We also highlight the need to improve our basic understanding of bottom-up processes, improve their representation within models, and ensure that our ecosystem models can capture growth limitation by nitrogen and other elements, and not just food/energy uptake.

Decline in Atlantic wolffish Anarhichas lupus in the North Sea : Impacts of fishing pressure and climate change - Joanna K. Bluemel; Simon H. Fischer; David W. Kulka; Christopher P. Lynam; Jim R. Ellis (Journal of Fish Biology, 2022)
Anarhichas lupus is a boreo‐Arctic species with biological characteristics often associated with vulnerability to overexploitation. Although not commercially targeted in the North Sea, A. lupus is a bycatch species in mixed demersal fisheries. Here we provide an overview of the status of A. lupus in the North Sea, as observed from commercial landings and fishery‐independent trawl survey data. A. lupus was once common across much of the central and northern North Sea but, since the 1980s, have declined in abundance, demographic characteristics (reduced size) and geographical range, with the shallower and more southerly parts of its range most impacted. A. lupus is still relatively frequent in the northern North Sea, where fishing intensity, though decreasing, is high. Bycatch through fishing remains a potential threat and, considering the likely impacts of predicted climate change on cold‐water species, risks of further regional depletion and/or range contraction remain. Whether or not A. lupus is able to re‐establish viable populations in former habitat in UK coastal waters is unknown. Given the lack of data, the precautionary principle would suggest that manageable pressures be minimized where the species and its habitat are at risk of further impacts, and more regular assessments of population status be undertaken.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Climate change alters fish community size‐structure, requiring adaptive policy targets - Ana M Queirós; José Fernandes; Lily Genevier; Christopher P Lynam (Fish and Fisheries, 2018)
Size‐based indicators are used worldwide in research that supports the management of commercially exploited wild fish populations, because of their responsiveness to fishing pressure. Observational and experimental data, however, have highlighted the deeply rooted links between fish size and environmental conditions that can drive additional, interannual changes in these indicators. Here, we have used biogeochemical and mechanistic niche modelling of commercially exploited demersal fish species to project time series to the end of the 21st century for one such indicator, the large fish indicator ( LFI ), under global CO 2 emissions scenarios. Our modelling results, validated against survey data, suggest that the LFI 's previously proposed policy target may be unachievable under future climate change. In turn, our results help to identify what may be achievable policy targets for demersal fish communities experiencing climate change. While fisheries modelling has grown as a science, climate change modelling is seldom used specifically to address policy aims. Studies such as this one can, however, enable a more sustainable exploitation of marine food resources under changes unmanageable by fisheries control. Indeed, such studies can be used to aid resilient policy target setting by taking into account climate‐driven effects on fish community size‐structure.

A decline in primary production in the North Sea over 25 years, associated with reductions in zooplankton abundance and fish stock recruitment - Elisa Capuzzo; Christopher P. Lynam; Jon Barry; David Stephens; Rodney M. Forster; Naomi Greenwood; Abigail McQuatters‐Gollop; Tiago Silva; Sonja M. van Leeuwen; Georg H. Engelhard (Global Change Biology, 2018)
Phytoplankton primary production is at the base of the marine food web; changes in primary production have direct or indirect effects on higher trophic levels, from zooplankton organisms to marine mammals and seabirds. Here, we present a new time‐series on gross primary production in the North Sea, from 1988 to 2013, estimated using in situ measurements of chlorophyll and underwater light. This shows that recent decades have seen a significant decline in primary production in the North Sea. Moreover, primary production differs in magnitude between six hydrodynamic regions within the North Sea. Sea surface warming and reduced riverine nutrient inputs are found to be likely contributors to the declining levels of primary production. In turn, significant correlations are found between observed changes in primary production and the dynamics of higher trophic levels including (small) copepods and a standardized index of fish recruitment, averaged over seven stocks of high commercial significance in the North Sea. Given positive (bottom‐up) associations between primary production, zooplankton abundance and fish stock recruitment, this study provides strong evidence that if the decline in primary production continues, knock‐on effects upon the productivity of fisheries are to be expected unless these fisheries are managed effectively and cautiously.

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

A Catalogue of Marine Biodiversity Indicators - Heliana Teixeira; Torsten Berg; Laura Uusitalo; Karin Fürhaupter; Anna-Stiina Heiskanen; Krysia Mazik; Christopher P. Lynam; Suzanna Neville; J. German Rodriguez; Nadia Papadopoulou; Snejana Moncheva; Tanya Churilova; et al. (Frontiers in Marine Science, 2016)

Uses of Innovative Modeling Tools within the Implementation of the Marine Strategy Framework Directive - Christopher P. Lynam; Laura Uusitalo; Joana Patrício; Chiara Piroddi; Ana M. Queirós; Heliana Teixeira; Axel G. Rossberg; Yolanda Sagarminaga; Kieran Hyder; Nathalie Niquil; Christian Möllmann; Christian Wilson; et al. (Frontiers in Marine Science, 2016)

Biodiversity in Marine Ecosystems—European Developments toward Robust Assessments - Anna-Stiina Heiskanen; Torsten Berg; Laura Uusitalo; Heliana Teixeira; Annette Bruhn; Dorte Krause-Jensen; Christopher P. Lynam; Axel G. Rossberg; Samuli Korpinen; Maria C. Uyarra; Angel Borja (Frontiers in Marine Science, 2016)

Bridging the Gap between Policy and Science in Assessing the Health Status of Marine Ecosystems - Angel Borja; Michael Elliott; Paul V. R. Snelgrove; Melanie C. Austen; Torsten Berg; Sabine Cochrane; Jacob Carstensen; Roberto Danovaro; Simon Greenstreet; Anna-Stiina Heiskanen; Christopher P. Lynam; Marianna Mea; et al. (Frontiers in Marine Science, 2016)

Distribution of skates and sharks in the North Sea: 112 years of change - Camilla Sguotti; Christopher P. Lynam; Bernardo García‐Carreras; Jim R. Ellis; Georg H. Engelhard (Global Change Biology, 2016)
How have North Sea skate and shark assemblages changed since the early 20th century when bottom trawling became widespread, whilst their environment became increasingly impacted by fishing, climate change, habitat degradation and other anthropogenic pressures? This article examines long‐term changes in the distribution and occurrence of the elasmobranch assemblage of the southern North Sea, based on extensive historical time series (1902–2013) of fishery‐independent survey data. In general, larger species (thornback ray, tope, spurdog) exhibited long‐term declines, and the largest (common skate complex) became locally extirpated (as did angelshark). Smaller species increased (spotted and starry ray, lesser‐spotted dogfish) as did smooth‐hound, likely benefiting from greater resilience to fishing and/or climate change. This indicates a fundamental shift from historical dominance of larger, commercially valuable species to current prevalence of smaller, more productive species often of low commercial value. In recent years, however, some trends have reversed, with the (cold‐water associated) starry ray now declining and thornback ray increasing. This shift may be attributed to (i) fishing, including mechanised beam trawling introduced in the 1960s–1970s, and historical target fisheries for elasmobranchs; (ii) climate change, currently favouring warm‐water above cold‐water species; and (iii) habitat loss, including potential degradation of coastal and outer estuarine nursery habitats. The same anthropogenic pressures, here documented to have impacted North Sea elasmobranchs over the past century, are likewise impacting shelf seas worldwide and may increase in the future; therefore, parallel changes in elasmobranch communities in other regions are to be expected.

Enhanced survival of 0-group gadoid fish under jellyfish umbrellas - Christopher P. Lynam; Andrew S. Brierley (Marine Biology, 2007)

Interannual variability in abundance of North Sea jellyfish and links to the North Atlantic Oscillation - Christopher P. Lynam; Stephen J. Hay; Andrew S. Brierley (Limnology and Oceanography, 2004)
Pronounced interannual variability in the abundance of medusae of the jellyfish species Aurelia aurita , Cyanea lamarckii , and Cyanea capillata (Phylum Cnidaria, Class Scyphozoa) in the North Sea was evident in data arising from the International Council for the Exploration of the Seas International 0‐group Gadoid Surveys between 1971 and 1986. Possible climatic forcing of jellyfish abundance, via the North Atlantic Oscillation (NAO), was investigated with data on medusae from four areas of the North Sea (east of Scotland, north of Scotland, east of Shetland, and west of northern Denmark). There were significant inverse relationships between medusa abundance and the NAO Index (December‐March) in two regions: west of northern Denmark ( A. aurita r 2 = 0.70, P = 0.003, n = 10; C. lamarckii r 2 = 0.74, P = 0.002, n = 10) and east of Scotland ( A. aurita r 2 = 0.53, P = 0.008, n = 12). Fluctuations in the abundance of A. aurita and C. lamarckii medusae might be linked to hydroclimatic changes induced through atmospheric effects (as encapsulated in the NAO Index) on wind stress, temperature, and currents. These fundamental hydroclimatic changes alter the timing of spring phytoplankton blooms and zooplankton community composition. Predation by an abundance of medusae on zooplankton and ichthyoplankton could affect the North Sea ecosystem through top‐down and bottom‐up mechanisms. Because the NAO is presently in a high phase, climatic conditions could be serving to depress the abundance of medusae: a future reversal of the NAO might favor jellyfish and weaken the persistence or recovery of fisheries.